Perkembangan gonad ikan betok (Anabas testudineus) betina yang diinduksi ekstrak hipofisa sapi - Tanbiyaskur Tanbiyaskur; Mirna Fitrani; Muhammad Fahrudin; Lutfi Lutfi; Muslim Muslim (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
The purpose of this study was to determine the effect of giving bull pituitary extract on the development of gonads of female broodstock of climbing perch (Anabas testudineus). The research method used a completely randomized design, four treatment doses of pituitary extract, namely 0.0; 0.1; 0.3; 0.6 ml/kg. Muscular injection of pituitary extract. The results showed that the dose of 0.6 ml/kg, the best performance of gonad development, where the egg diameter was 0.640 mm, the somatic index was 4.22%, the hepatosomatic index was 0.18% and the total fecundity was 6404 eggs. Water quality parameters during fish rearing are in a good range for gonad development of climbing perch fish.